ANALISIS NILAI LOG GAMMA RAY DAN LOG DENSITY TERHADAPVARIASI KECEPATAN PEREKAMAN METODE WELL LOGGING “ROBERTSON GEOLOGGING (RG)” - Khasanah, Ulfiatul; Supriyanto, Supriyanto; Djayus, Djayus (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2019)
The lithology of rocks in the subsurface can be known from the results of analysis of coring and geophysical logging. The activity of recording data geophysical logging in the work area of PT. Mintec Abadi generally uses a velocity of 3 m/minute - 4 m/minute with drill depths and different location points. The purpose of this study was to determenite the lithology pattern of rocks based on curves gamma ray log and density with record velocity variation of geophysical logging, and what is the optimal velocity. Records of data geophysical logging (Log Gamma Ray and Density Log) on well log tests with velocity variation, in the same lithology range of rocks, analyzed by the structure and pattern of the lithology, and compared to other velocity. The results of this study shows the lithological pattern of the record velocity variation (1.5 m/minute – 10 m/minute) give relatively the same results with the lithology arrangement is top soil, mudstone, coal and muddy sandstone. The optimal velocity of geophysical logging based on conditions in the work area of PT. Mintec Abadi between 5 m/minute – 7 m/minute.